Readiness of higher education leaders to implement micro-credentials in Malaysia - Rami, Ahmad Aizuddin Md; Ismail, Ismi Arif; Sarman, Mohd Amin; Aziz, Mohd Faiq Abd; Zulkifly, Nurul Afiqah (Institute of Advanced Engineering and Science, 2024)
Higher education institutions (HEIs) have invested considerable effort in integrate micro-credentials into educational systems framework. However, the readiness of middle leaders and lecturers to effectively support these initiatives remains uncertain. Furthermore, research on the preparedness of coordinators as middle leaders in HEIs is still limited. To address this gap, a study was conducted to explore the readiness of middle leaders for implementing micro-credentials in HEIs. This research involved five informants who serve as coordinators and program leaders within their faculties. The study utilized focus group discussions to deeply investigate the readiness of these leaders, providing valuable insights into their current level of preparedness and their ability to effectively support the implementation of micro-credential programs. The analysis of the data resulted in the identification of five major themes: i) the conceptualization of micro-credentials; ii) training and development; iii) infrastructure; iv) quality; and v) institutional readiness, all of which represent challenges faced by university leaders. The study underscores the importance of top university leaders demonstrating a clear vision and unwavering commitment, which are crucial for the implementation of micro-credentials within the higher education institutions landscape.